The presentation of the judicial actor in everyday life: a first approach to the public defense in the jury trial - Kostenwein, Ezequiel (DIXI, 2026)
This work is part of a broader set of empirical research on criminal justice in Argentina. Specifically, it seeks to contribute to understanding the functioning of the Public Defender’s Office in the context of jury trials, given that this is an ambitious undertaking for the judicial administration and relatively new in the country. The study draws on interviews with members of the Public Defender’s Office, together with direct observation of the debates that take place in jury trials, in order to analyze what happens in practice.
Keywords: Public Defender’s Office; criminal justice; jury trials; practice